Improving the Literal Reading Comprehension Ability of Grade IV Students through the Use of Digital Comic Media in Elementary Schools - Vevy Liansari (Academic Bright Collaboration, 2026)
Purpose - This study aimed to analyze the effectiveness of digital comic media in improving the literal reading comprehension skills of fourth-grade elementary school students, particularly in understanding explicit information presented in reading texts.Method - The study employed a quantitative approach with a pre-experimental one-group pretest-posttest design. The participants consisted of 30 fourth-grade students selected using a saturated sampling technique. The research instrument was a 30-item multiple-choice test based on four indicators of literal comprehension: identifying main ideas, locating detailed information, sequencing events, and recognizing cause-and-effect relationships. The instrument was reviewed by two elementary literacy experts and tested for validity and reliability. The intervention was conducted over four learning sessions using digital comics as instructional media in Indonesian language lessons. Data were analyzed using the Shapiro-Wilk normality test and a paired-sample t-test.Findings - The findings revealed a substantial improvement in students’ literal reading comprehension skills. The mean score increased from 45.83 on the pretest to 85.00 on the posttest. The paired-sample t-test showed a statistically significant difference between pretest and posttest scores (p < 0.05), indicating that students’ literal reading comprehension improved after the implementation of digital comic media.Research Implications - These findings suggest that digital comic media can support the improvement of elementary students’ literal reading comprehension skills. However, further studies employing control groups and stronger experimental designs are recommended to provide more robust evidence of its effectiveness.Originality - This study contributes to research on digital learning media by specifically examining the use of digital comics to improve literal reading comprehension among fourth-grade elementary school students through four measured indicators of comprehension.